2009
DOI: 10.1007/s00542-009-0923-1
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of process-parameter and part-geometry effects on the quality of filling in micro-injection moulding

Abstract: This paper addresses the use of micro-injection moulding for the fabrication of polymeric parts with microfeatures. Five separate parts with different micro-feature designs are moulded of Polymethylmethacrylate. The design-of-experiments approach is applied to correlate the quality of the parts to the processing parameters. Five processing parameters are investigated using a screening half-factorial experimentation plan to determine their possible effect on the filling quality of the moulded parts. The part ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Attia et al [6] considered part mass as output parameter. The five processing parameters investigated were melt temperature, mould temperature, injection speed, holding pressure and cooling time.…”
Section: Adoption Of Part Mass As a Parameter At The Micro-scalementioning
confidence: 99%
“…Attia et al [6] considered part mass as output parameter. The five processing parameters investigated were melt temperature, mould temperature, injection speed, holding pressure and cooling time.…”
Section: Adoption Of Part Mass As a Parameter At The Micro-scalementioning
confidence: 99%
“…Data analysis and optimization was conducted with Minitab ® 15 [23]. Procedures for selecting the levels for each factor are available in the literature [10]. Table 2.…”
Section: Component Geometriesmentioning
confidence: 99%
“…Quality parameters (responses) are usually associated with evaluating the replication fidelity of the processes by completely filling the mould cavity. Typical responses include filling quality of micro-sized channels [2], feature dimension [3][4][5][6], part mass [7][8][9][10][11], flow length [12,13], filling volume fraction [14], weld-line formation [15], demoulding forces [16] and minimising injection time, pressure and temperature distribution using a three-dimensional simulation package [17].…”
Section: Introductionmentioning
confidence: 99%
“…Viscosity is the dominant factor among all rheological properties to cause severe effects on polymer melting flow capability in processing and molding. With the continuous development of simulation of molding process and composite polymer processing, it is more necessary to obtain reliable rheological data, especially shear viscosity …”
Section: Introductionmentioning
confidence: 99%
“…With the continuous development of simulation of molding process and composite polymer processing, 2,3 it is more necessary to obtain reliable rheological data, especially shear viscosity. [3][4][5] However, viscosity measurements of non-Newtonian polymer melts are affected by molecular characteristics, geometries, temperature, wall slip, and so on. For example, the blend of branched polypropylene and linear polypropylene was compared with that of linear polypropylene by J. Drabek et al Results showed that the blend has an expected higher shear viscosity compared to the linear polypropylene due to dominantly higher number of entanglements.…”
Section: Introductionmentioning
confidence: 99%